The design and development of driving game as an evaluation instrument for driving license test - Abdul Hadi, Abdul Razak; Manap, Mohd Hairy (World Academy of Science, Engineering and Technology, 2013)
The focus of this paper is to highlight the design and development of an educational game prototype as an evaluation instrument for the Malaysia driving license static test.This educational game brings gaming technology into the conventional objective static test to make it more effective,real and interesting.From the feeling of realistic the future driver can learn something , memorized and use it in the real life.The current online objective static test only make the user memorized the answer without knowing and understand the true purpose of the question.Therefore, in real life they will not behave as expected due to behavior and moral lacking.This prototype has been developed inform of multiple-choice questions integrated with 3D gaming environment to make it simulate the real environment and seenarios.Based on the testing conducted the respondent agrees with the use of this game prototype it can increase understanding and promote obligation towards traffic rules.